Perbandingan Rasio Kinerja Keuangan Perusahaan Energi Industri yang Terdaftar di Bursa Efek Indonesia pada Periode 2020-2022 - Anastasya Mechta Mediana; Herny Ria Mandag; Naafika Rachma Rozani; Cholis Hidayati (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This study aims to evaluate the financial performance of energy industry companies, with a focus on PT. PLN (Persero), Tbk, PT. Pertamina (Persero), Tbk, and PT. Indika Energy, Tbk, for the period 2020-2022. The research method used is a quantitative method because the research data is in the form of numbers and the analysis uses statistics. Through the financial ratio analysis approach, this study uses time series and cross-sectional methods to compare the financial performance of companies with the average industry ratio. The results of the analysis concluded that PT. Pertamina showed the best performance, followed by PT. Indika Energy, while PT. PLN had the lowest performance. Factors such as revenue, operational efficiency, and debt dependence affect the financial performance of each company.